Magnetic Resonance–Guided Focused Ultrasound Thalamotomy May Spare Dopaminergic Therapy in Early‐Stage Tremor‐Dominant Parkinson's Disease: A Pilot Study. Issue 11 (29th August 2022) - Golfrè Andreasi, Nico; Cilia, Roberto; Romito, Luigi Michele; Bonvegna, Salvatore; Straccia, Giulia; Elia, Antonio Emanuele; Novelli, Alessio; Messina, Giuseppe; Tringali, Giovanni; Levi, Vincenzo; Devigili, Grazia; Rinaldo, Sara; et al.
ABSTRACT: Background: Magnetic resonance–guided focused ultrasound (MRgFUS) thalamotomy is a safe and effective procedure for drug‐resistant tremor in Parkinson's disease (PD). Objective: The aim of this study was to demonstrate that MRgFUS ventralis intermedius thalamotomy in early‐stage tremor‐dominant PD may prevent an increase in dopaminergic medication 6 months after treatment compared with matched PD control subjects on standard medical therapy. Methods: We prospectively enrolled patients with early‐stage PD who underwent MRgFUS ventralis intermedius thalamotomy (PD‐FUS) and patients treated with oral dopaminergic therapy (PD‐ODT) with a 1:2 ratio. We collected demographic and clinical data at baseline and 6 and 12 months after thalamotomy. Results: We included 10 patients in the PD‐FUS group and 20 patients in the PD‐ODT group. We found a significant increase in total levodopa equivalent daily dose and levodopa plus monoamine oxidase B inhibitors dose in the PD‐ODT group 6 months after thalamotomy. Conclusions: In early‐stage tremor‐dominant PD, MRgFUS thalamotomy may be useful to reduce tremor and avoid the need to increase dopaminergic medications. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society